Acerca del referente último del Ṛg Veda - Hernández Quiroz, Anselmo (El Colegio de México, 2019)
The most recent translations of the Ṛg-Veda consider this text as an exemplary liturgical poem or religious literature. However, it does not clearly discuss the parameters with which it is classified as being religious. This raises an important question once again: Is the Ṛg-Veda a religious text? Is it connected to some kind of religion? This paper researches the issue of the last reference as expressed in the Ṛg-Veda, referring to the existence of homogenously distributed passages both of textual determination and indetermination. Therefore, given the impossibility of a rigorous discussion of complete determination and indetermination, the final reference described is not defined. For that reason, I consider that the most ancient Vedic thought—as confirmed in the Ṛg-Veda—differs from both religious and philosophical thought, as these remain defined by the concepts of “God” and “principle”. In contrast, the author proposes an approach to the most ancient Vedic thought as a model of initiatory poetry.